Click, Store, Emit: The Environmental Cost of Digital Infrastructure - Al‑Sowaidi, Albandari; Isaifan, Rima J. (Digital Technologies Research and Applications, 2025)
The accelerating expansion of digital infrastructure, including data centers, communication networks, and Artificial Intelligence (AI) systems, is transforming economies and societies worldwide. However, this digital transformation carries a growing environmental cost, particularly in terms of carbon emissions, resource consumption, and lifecycle waste. This literature review critically explores the environmental footprint of digital infrastructure, with a primary focus on carbon emissions across the stages of manufacturing, operation, and disposal. While studies from China dominate the empirical base due to its rapid digitalization, the review incorporates comparative evidence from Europe and North America to strengthen its global applicability. Key sources of emissions are identified in energy‑intensive operations such as data center cooling and AI model training. To mitigate these impacts, this study examines integrated strategies including renewable energy deployment, nanotechnology‑based cooling innovations, Environmental, Social, and Governance‑driven policy frameworks, and circular economy applications. A revised research framework is proposed to guide future investigation into sustainable digitalization. Moreover, this review emphasizes the importance of public participation in smart city governance, advocating for co‑created urban solutions, open data platforms, and inclusive digital planning. By embedding solution pathways throughout the discussion, the paper presents a cohesive analysis that bridges technological innovation with climate and environmental priorities. Ultimately, this concludes with recommendations for cross‑sectoral collaboration among governments, industries, and communities to ensure that digital progress aligns with long‑term sustainability goals.